USE OF CALCIUM HYDROXIDE AS AN ANTIMICROBIAL AGENT IN ENDODONTICS - Wahid, Abdul (Journal of Ayub Medical College Abbottabad, 1990)
ABSTRACT: Antimicrobial activities of calcium hydroxide were observed in 30 chronically infected root canals in comparison with 2% iodine potassium iodide. It was noted that antimicrobial activities of calcium hydroxide and 2% iodine potassium iodide were similar.